Shifting Geothermal Prudence in Law 21/2014 and Job Creation Law for NDC - Dwi Najah Tsirwiyati (IHSA Institute, 2026)
Indonesia is a country rich in geothermal potential. In the regulations governing geothermal energy, Indonesia has experienced a shift in regulations that have an impact on the application of the principle of prudence in geothermal land use projects. This regulatory shift is very important to realize the Nationally Determined Contribution (NDC). This study analyzes the evolution of the normative framework between Law No. 21/2014 and the Job Creation Law on the principle of prudence by using historical, statute, comparative, and conceptual approaches. Law No. 21/2014, which was previously the legal basis for geothermal energy, has integrated the principle through strict licensing and strict environmental supervision. The law emphasizes proactive risk mitigation. However, on the contrary, the Job Creation Law through the Risk-Based Approach (RBA) and Online Single Submission (OSS) actually prioritizes accelerating investment and simplifying bureaucracy, This has the potential to weaken environmental damage prevention measures because it only relies on predetermined risk standards. This certainly risks eroding the core principle of the precautionary principle: prudent action in the midst of scientific uncertainty. The study evaluated the effectiveness of both regimes in balancing the energy transition with ecological protections for NDC targets